Medical liver biopsy: background, indications, procedure and histopathology. Issue 1 (2nd March 2019) - Boyd, Alexander; Cain, Owen; Chauhan, Abhishek; Webb, Gwilym James
Abstract : Histological analysis of liver tissue continues to play an important role in modern hepatological practice. This review explores the indications for medical liver biopsy in addition to the procedure itself, potential complications, preparation of tissue and routine staining. A broad selection of histological images is included to illustrate the appearance of liver tissue both in health and in several important diseases.